The feasibility of adopting Islamic Banking system under the existing laws in Uganda - Lujja, Sulaiman; Mohammed, Mustafa Omar; Hassan, Rusni; Oseni, Umar Aimhanosi (Emerald Group Publishing Limited, 2016)
Purpose – In 2014, Islamic finance assets are estimated to have exceeded US$2 trillion with over 100 products and an annual growth of over 20.7 per cent, across more than 76 countries, most of which are members of the Organization of Islamic Cooperation (OIC). Despite this remarkable market expansion, numerous OIC members such as Uganda are yet to fully adopt this unique financial system because of regulatory constraints. Thus, the purpose of this paper is to examine the extent to which Uganda can benchmark the Malaysian experience and best practices to overcome the regulatory challenges in introducing Islamic Banking.Design/methodology/approach – This exploratory study adopts qualitative research methods through documentary review to elicit relevant information from the existing laws in Uganda that would accommodate the Islamic Banking system. Interpretive analysis and analytical methods are used to analyze data. Findings – The Malaysian experience and best practices of Islamic Banking regulation need to be benchmarked by regulators. Relevant laws which require some amendments include section 37(a) and 38(1) of the Financial Institutions Act 2004 and section 29(3)(a) of the Bank of Uganda Act 2000. Similarly, tax legislation needs amendments to ensure a level playing field for Islamic finance and conventional finance products. Originality/value – This is one of the earliest studies on models of Islamic Banking regulation suitable for adoption in Uganda. This study contributes to literature on how other jurisdictions (especially those with less regulatory prudence) could regulate Islamic Banking in a dual banking system jurisdiction.